The Effect of Additional Skipjack Gills on The Quality of Compost Aerobic Composting Process - Dwi Wahyu Purwiningsih; Susan Arba (Politeknik Kesehatan Kemenkes Jakarta II, 2020)
Waste is the residue of daily activities human days and/or solid natural processes. The solid waste generated by Ternate city people transported to TPA is 226 m3/ day, with a service level of 57% of the total population of Ternate City. Alternative waste management is better for dealing with this problem, one of them by using processing waste into compost. The purpose of this study was to determine the additional effect of skipjack gills on the physical quality of compost in the aerobic composting process. This type of research is an experimental study with a posttest only control design. The results of this study are the quality of compost with the addition of skipjack fish is good because the NPK measurement results are by SNI 2803: 2010, with the results of N: 8%, P: 9% and K: 9%. And for measurements of temperature, humidity, and pH following SNI: 19-7030-2004. Suggestions for further research are to be developed further.